Citrus flavanones enhance the bioaccessibility of β-carotene by improving lipid lipolysis and incorporation into mixed micelles. (December 2021) - Xiao, Yaru; Nie, Meimei; Zhao, Hongwei; Li, Dajing; Gao, Ruichang; Zhou, Cunshan; Xu, Yayuan; Dai, Zhuqing; Zhang, Zhongyuan
Graphical abstract: Highlights: Citrus flavanones can promote the bioaccessibility of β-carotene, independently of the type of oil studied. Citrus flavanones can promote lipid hydrolysis by reducing the size of micelles. Citrus flavanone and bile salt synergistically promote β-carotene to enter micelles. Citrus flavanones can significantly promote β-carotene cell absorption. Abstract: Flavonoids can influence the bioaccessibility of carotenoids. In this study, the effect of citrus flavanones on β-carotene (Bc) bioaccessibility, lipid lipolysis and Bc micellarization were investigated. The results show that citrus flavanones significantly increased the bioaccessibility of Bc, made it from 15.85% to 19.67% (p < 0.05). The extent hydrolysis of different oil was significantly increased in the presence of citrus flavanones. In the case of soybean oil, addition of hesperetin (Hes) increased the extent hydrolysis of oil by 19.2% for 120 min ( p <  0.05). Addition of citrus flavanones promoted the Bc micellarization. Data showed that citrus flavanones resulted in decrease of particle size and increase the absolute value of the emulsion ζ-potential, which could be partially responsible for the increase of hydrolysis of lipid and the Bc micellarization. Furthermore, cell experiments could clearly show that citrus flavanones can enhance the absorption of Bc in cells.